Kevlar-Alumina Composite as An Alternative Substrate for 5G Antenna Application - Efrilia Ma'rifatul Khusna; Subagio Budi Basuki; Hutama Arif Bramantyo (Politeknik Negeri Malang, 2022)
This paper introduces a millimetre-wave antenna design for 5G application using an alternative substrate called Kevlar-Alumina Composite. Kevlar-Alumina Composite had been researched and measured comprehensively by Indonesian Institute of Science (LIPI) Bandung showing dielectric value of 9.2. The application of the antenna geometry is based on Vivaldi Coplanar antenna with L shaped feeding on the ground plane. Vivaldi Antenna is chosen as it has a relatively small size with various structures. An antenna of 3.75 GHz for 5G application using Kevlar-Alumina Composite is proposed. The simulated results of single-element 5G antenna have return loss value of -21.949 dB, 1.173 VSWR, directive radiation pattern at E-Plane and H-plane, and surface current. The use of the Kevlar-Alumina Composite performed good results.